2022
DOI: 10.1109/tvt.2022.3184514
|View full text |Cite
|
Sign up to set email alerts
|

Uncertainty Modeling for Participation of Electric Vehicles in Collaborative Energy Consumption

Abstract: This paper proposes an accurate and efficient probabilistic method for modeling the nonlinear and complex uncertainty effects and mainly focuses on the Electric Vehicle (EV) uncertainty in Peer-to-Peer (P2P) trading. The proposed method captures the uncertainty of the input parameters with a low computational burden and regardless of the probability density function (PDF) shape. To this end, for each uncertain parameter, multitude of random vectors with the specification of corresponding uncertain parameters a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
8
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(8 citation statements)
references
References 39 publications
0
8
0
Order By: Relevance
“…Traditional methods can be categorized into four main types, taking into account node information and network structure. (1) The first approach focuses on the local network structure, such as degree centrality [3], which evaluates node importance based on their degree. Nodes with higher degrees are regarded as more critical due to they enhance the connectivity of the network.…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…Traditional methods can be categorized into four main types, taking into account node information and network structure. (1) The first approach focuses on the local network structure, such as degree centrality [3], which evaluates node importance based on their degree. Nodes with higher degrees are regarded as more critical due to they enhance the connectivity of the network.…”
Section: Introductionmentioning
confidence: 99%
“…Artificial intelligence-based methods can be categorized into two main types. (1) The first approach applies machine learning-based methods to identify critical nodes, such as LS-SVM [10] and decision trees [11]. (2) The second approach employs deep learning-based methods, such as RCNN [12] and InfGCN [13].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Few studies assessed the impacts of CET on LVDN if the grid constraints were not included in the model. These studies assessed the impacts of CET on different components and operation limits of LVDNs, such as peak demand, losses, voltage deviations, congestions of distribution network components, and voltage unbalance [6], [8]- [14]. The results of these studies showed that under low DER penetration levels and low local energy trading, no violations of grid constraints occur.…”
Section: Introductionmentioning
confidence: 99%
“…However, this study did not consider the connection of ESS and EVs simultaneously at the LVDN. Ref [35] assessed the impact of CET on LVDN voltage considering the presence of PV, WG, ESS, and EVs. The study found that the voltage was within acceptable limits.…”
Section: Introductionmentioning
confidence: 99%